2017
DOI: 10.1149/2.0351709jss
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning Solutions for Ultrathin Co Barriers for Advanced Technology Nodes

Abstract: Co, a candidate material for barrier and capping layers in 10 nm and smaller Cu interconnects, is prone to corrosion and galvanic corrosion during chemical mechanical planarization (CMP) and wet cleaning in aqueous environments posing a serious challenge to its use since the Co liner in the advanced nodes is desired to be only ∼2 to 3 nm thick. We show that E corr between Cu and Co (2 nm) films can be reduced to <10 mV, with Cu being more noble, in an aqueous solution of 6.6 mM (0.05 wt%) Glycine + 15 mM 1,2,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…should be avoided during polishing. Since this is not always possible, post-CMP cleaning has become a crucial step to eliminate many of these defects [141,142,143,144]. Recently, the author not only showed that the rupture of a strong chemical bonding between abrasive particles and the SiO 2 films via a nucleophilic attack could help remove the particles from the surface [141] but also reported a stability constant-based strategy to study reagents that can remove Cu-BTA and Co-BTA complexes from various surfaces (Cu, Co, TaN, and SiO 2 films) [109,110].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…should be avoided during polishing. Since this is not always possible, post-CMP cleaning has become a crucial step to eliminate many of these defects [141,142,143,144]. Recently, the author not only showed that the rupture of a strong chemical bonding between abrasive particles and the SiO 2 films via a nucleophilic attack could help remove the particles from the surface [141] but also reported a stability constant-based strategy to study reagents that can remove Cu-BTA and Co-BTA complexes from various surfaces (Cu, Co, TaN, and SiO 2 films) [109,110].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…In some cases, the alumina particles (pH IEP ~ 7) are used as the abrasive for W CMP, and they are observed on the W films after polishing due to its positive charge in the acidic medium [13,24]. Co films and other metal films can also be contaminated with the silica abrasive during polishing [14,15]. These particle contaminants can be controlled by the chemical reactions between slurry components and films being polished.…”
Section: Residual Abrasive Particlesmentioning
confidence: 99%
“…are presented on the polished wafer surfaces. The removable defects, also known as CMP-related to contaminants, should be completely removed in the subsequent cleaning process while minimizing the further formation of non-removable defects [14,15]. CMP consumables themselves can be the source of the contaminants during polishing and cleaning [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore Ru CMP has a lot of limitation to achieve enough removal rate by CMP. Cobalt (Co) is the most potential candidate metal for replacing tungsten as contact metal (or replacing Ta/TaN as barrier metal) and its CMP slurry abrasive development is upmost challenge for device fabrication [52][53][54]. Known issues by Co CMP are residual abrasive particle defects and Co corrosion.…”
Section: Advanced Abrasives For Future Cmp Applicationsmentioning
confidence: 99%